2019
DOI: 10.4292/wjgpt.v10.i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab and Nivolumab induced steroid-refractory colitis treated with infliximab: A case report

Abstract: BACKGROUNDA variety of immune-modulating drugs are becoming increasingly used for various cancers. Despite increasing indications and improved efficacy, they are often associated with a wide variety of immune mediated adverse events including colitis that may be refractory to conventional therapy. Although these drugs are being more commonly used by Hematologists and Oncologists, there are still many gastroenterologists who are not familiar with the incidence and natural history of gastrointestinal immune-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Based on the CTCAE grading scale, our patient would be categorized as grade 2 colitis, due to mucus in the stool, and grade 4 diarrhea, due to severe electrolyte derangement with profound widening of the Q-R-S complex evidenced by QTc prolongation (see Table 1). Previous case reports have described severe colitis secondary to combined ipilimumab and nivolumab therapy refractory to high-dose steroid therapy [3]. While our patient demonstrated a rapid improvement after initiation of steroids, up to 40% of cases may require initiation of infliximab as a second-line therapy (4).…”
Section: Discussionmentioning
confidence: 54%
“…Based on the CTCAE grading scale, our patient would be categorized as grade 2 colitis, due to mucus in the stool, and grade 4 diarrhea, due to severe electrolyte derangement with profound widening of the Q-R-S complex evidenced by QTc prolongation (see Table 1). Previous case reports have described severe colitis secondary to combined ipilimumab and nivolumab therapy refractory to high-dose steroid therapy [3]. While our patient demonstrated a rapid improvement after initiation of steroids, up to 40% of cases may require initiation of infliximab as a second-line therapy (4).…”
Section: Discussionmentioning
confidence: 54%
“…If no response to high-dose steroids, or if relapse requires an increase in steroid dosing during the tapering period, such cases are considered refractory [4]. In cases of refractory colitis, four different medications were investigated in recent studies, which include: infliximab, mycophenolate, and Entyvio [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the CTCAE grading (severity) scale, the treatment options may vary from the symptomatic treatment of diarrhea with loperamide and electrolyte repletion to the initiation of immunosuppressive agents [4]. In the case of refractory colitis, multiple studies have shown a response to infliximab, mycophenolate, cyclosporine, and Entyvio [5][6][7][8]. We present a case of refractory colitis to both infliximab and Entyvio, treated with a high-dose steroid (methylprednisolone) and mycophenolate.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, steroid therapy with approximately 1 mg/kg/day prednisolone (PSL) equivalent is immediately initiated for grade 3 diarrhea/colitis. However, when symptoms do not improve, infliximab (IFX) treatment, generally at a dose of 5 mg/kg/day according to the Efficacy and safety of Infliximab for steroid-resistant immune-related adverse events: A retrospective study administration for ulcerative colitis (3)(4)(5)(6)(7)(8)(9)(10)(11), has been recommended. Single-dose IFX administration has often been selected as an irAE treatment, with additional doses administered only when no improvements occur after the first dose.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is imperative to pre-emptively identify symptoms of medium-and long-term adverse reactions such as infectious diseases, demyelinating diseases, aplastic anemia, malignant tumors, autoimmune diseases, and heart failure, among which infectious diseases are of particular concern. Several case reports have described successful treatment of steroid-resistant ICI-induced diarrhea/colitis with IFX in patients receiving ipilimumab (IPI), an anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4) antibody preparation (3)(4)(5)(6), as well as anti-programmed cell death-1 (PD-1) antibody or anti-programmed cell death-ligand 1 (PD-L1) antibody preparations (7)(8)(9)(10)(11). However, we were unable to identify any report systematically dealing with the required number of IFX doses or the time to switch to after treatment.…”
Section: Introductionmentioning
confidence: 99%